854 SODIUM NITROPRUSSIDE IN ACUTE HEART FAILURE: EFFECTS ON LV AFTERLOAD AND VENTRICULO-ARTERIAL COUPLING. (15th December 2022) - Baldetti, Luca; Gagliardi, Maria Felicia; Boccellino, Antonio; Calvo, Francesco; Pazzanese, Vittorio; Gramegna, Mario; Sacchi, Stefania; Cappelletti, Alberto
Abstract: Background: Acute heart failure (AHF) with left ventricle (LV) dysfunction is characterized by a condition of afterload mismatch without preload reserve. LV ejection fraction (LVEF) and stroke volume (SV) become thus dependent on the afterload. Owing to its arteriolar vasodilator properties, sodium nitroprusside (SNP) may reduce LV afterload and result particularly beneficial in this setting, improving LV ejection and ventriculo-arterial coupling (VAC). Hypothesis: We aimed to assess the effect of SNP on LV afterload (arterial elastance, Ea), LV contractility (end-systolic elastance, Ees) and VAC (Ea/Ees ratio) in AHF patients. Methods: Patients with AHF receiving SNP were prospectively enrolled and underwent Ea and Ees estimation with a single-beat echocardiographic method, before and after SNP infusion. The method was described by Chen et al (J Am Coll Cardiol, 2001) and Kelly et al (Circulation, 1992). Echocardiography was analyzed by a physician blinded to the images timing. Results: A total of 36 AHF patients [69% male, age 70 (68, 76) years] received SNP infusion and were enrolled. Patients were admitted for acute coronary syndrome (47%) and for worsening heart failure (53%). SNP median dose was low: 0.30 (0.21-0.57) mcg/kg/min. SNP led to a trend to SBP reduction [140 (131-150) vs 158 (140-168) mmHg; p=0.002]. Heart rate did not change: 84 (75, 92) vs 83 (72, 94) bpm; p=0.800. Afterload (Ea) was reduced following SNP infusion: 2.2 (1.9, 2.7) vs 2.8 (2.4, 3.4) mmHg/mL; p<0.001. LV contractility (Ees) was unchanged: 1.3 (0.8, 2.2) vs 1.5 (0.9, 3.4) mmHg/mL; p=0.13. End-diastolic volume did not change: 148 (110, 205) vs 146 (108, 213) mL; p=0.880. These effects led to an increased SV: 56 (47, 67) vs 50 (38, 56) mL; p<0.001; p<0.001 and, subsequently to an increased EF [40 (30, 50) vs 30 (20, 40)%; p<0.001]. The VAC did not significantly change after SNP infusion: 1.5 (0.9-2.8) vs 1.6 (0.9-2.7); p=0.64. Conclusion: In this report on consecutive AHF, low-dose SNP did not significantly affect VAC but led to a significant reduction in LV afterload and to a significant increase in SV and LVEF.